2022
DOI: 10.3389/fendo.2022.817825
|View full text |Cite
|
Sign up to set email alerts
|

No Differences in Value-Based Decision-Making Due to Use of Oral Contraceptives

Abstract: Fluctuating ovarian hormones have been shown to affect decision-making processes in women. While emerging evidence suggests effects of endogenous ovarian hormones such as estradiol and progesterone on value-based decision-making in women, the impact of exogenous synthetic hormones, as in most oral contraceptives, is not clear. In a between-subjects design, we assessed measures of value-based decision-making in three groups of women aged 18 to 29 years, during (1) active oral contraceptive intake (N = 22), (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…A growing body of research supports the tenet that oral contraceptives impact cognition and alter brain function in task- and composition- dependent manners (e.g., Gogos, 2013 ; Egan and Gleason, 2012 ; Beltz et al, 2015 , 2022 ; Porcu et al, 2019 ; Taylor et al, 2020 ; Ycaza Herrera et al, 2020 ; Gravelsins et al, 2021 ; Lewis et al, 2022 ; Menting-Henry et al, 2022 ). Overall, the current series of experiments found that the spironolactone-derived progestin drospirenone has beneficial effects for spatial working memory performance in a young adult Ovx rat model, and that the synthetic estrogen EE has variable effects on behavior that depend on dose and combination with drospirenone.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research supports the tenet that oral contraceptives impact cognition and alter brain function in task- and composition- dependent manners (e.g., Gogos, 2013 ; Egan and Gleason, 2012 ; Beltz et al, 2015 , 2022 ; Porcu et al, 2019 ; Taylor et al, 2020 ; Ycaza Herrera et al, 2020 ; Gravelsins et al, 2021 ; Lewis et al, 2022 ; Menting-Henry et al, 2022 ). Overall, the current series of experiments found that the spironolactone-derived progestin drospirenone has beneficial effects for spatial working memory performance in a young adult Ovx rat model, and that the synthetic estrogen EE has variable effects on behavior that depend on dose and combination with drospirenone.…”
Section: Discussionmentioning
confidence: 99%